Estimating the effects of the container revolution on world trade - Bernhofen, Daniel M.; El-Sahli, Zouheir; Kneller, Richard (Elsevier, 2015)
Many historical accounts have asserted that containerization triggered complementary technological and organizational changes that revolutionized global freight transport. We are the first to suggest an identification strategy for estimating the effects of the container revolution on world trade. Our empirical strategy exploits time and cross-sectional variation in countries’ first adoption of container facilities and combines it with product-level variation in containerizability and container usage. Applying our container variables on a large panel of product level trade flows for the period 1962-1990, our estimates suggest economically large concurrent and cumulative effects of containerization and lend support for the view of containerization being a driver of 20th century economic globalization.